Optineurin is required for CYLD-dependent inhibition of TNFα-induced NF-κB activation. - Ananthamurthy Nagabhushana (Public Library of Science (PLoS), 2011)
The nuclear factor kappa B (NF-κB) regulates genes that function in diverse cellular processes like inflammation, immunity and cell survival. The activation of NF-κB is tightly controlled and the deubiquitinase CYLD has emerged as a key negative regulator of NF-κB signalling. Optineurin, mutated in certain glaucomas and amyotrophic lateral sclerosis, is also a negative regulator of NF-κB activation. It competes with NEMO (NF-κB essential modulator) for binding to ubiquitinated RIP (receptor interacting protein) to prevent NF-κB activation. Recently we identified CYLD as optineurin-interacting protein. Here we have analysed the functional significance of interaction of optineurin with CYLD. Our results show that a glaucoma-associated mutant of optineurin, H486R, is altered in its interaction with CYLD. Unlike wild-type optineurin, the H486R mutant did not inhibit tumour necrosis factor α (TNFα)-induced NF-κB activation. CYLD mediated inhibition of TNFα-induced NF-κB activation was abrogated by expression of the H486R mutant. Upon knockdown of optineurin, CYLD was unable to inhibit TNFα-induced NF-κB activation and showed drastically reduced interaction with ubiquitinated RIP. The level of ubiquitinated RIP was increased in optineurin knockdown cells. Deubiquitination of RIP by over-expressed CYLD was abrogated in optineurin knockdown cells. These results suggest that optineurin regulates NF-κB activation by mediating interaction of CYLD with ubiquitinated RIP thus facilitating deubiquitination of RIP.